Burnout syndrome in healthcare profession - Bednáriková, Miroslava; Libová, Lubica; Kollárová, Lívia; Zacharová, Lenka (Magyar Gerontológia, 2022)
Burnout syndrome is a current topic. Helping professions are most at risk. We include the profession of nurse to these professions. The work is demanding, it requires mental endurance and physical fitness. Nursing profession is one of the most risky one in relation to burnout syndrome.